PERAN PENYULUH DALAM KEBERDAYAAN PETANI PADI SAWAH DI DESA BELADING KECAMATAN SABAK AUH KABUPATEN SIAK - Cepriadi, Cepriadi; Kausar, Kausar (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2021)
Farmers can optimize their agricultural products and improve their farming, it is necessary for the role of extension workers to provide education and guidance to farmers so that farmers can work on land and produce optimal agricultural products so that farmers can be successful in their farming business. To improve their farming business, farmers need the role of agricultural extension workers. Agricultural extension agents are agents of change who are directly related to farmers. The main function of the extension worker is to change the attitude of the farmer through non-formal education so that the farmer has a better life in a sustainable manner. This study aims to analyze the influence of the role of extension workers on farmer empowerment. This research was conducted in Belading Village, Sabak Auh District, Siak Regency. Respondents in this study were lowland rice farmers who joined farmer groups as many as 50 samples. To answer the purpose of this study using multiple linear regression analysis. The results showed that the role of the extension worker had a significant effect on the empowerment of lowland rice farmers in the village of Belading either simultaneously or partially.